Active proportional feedback control of turbulent flow over a circular cylinder with averaged velocity sensor - Yun, Jinhyeok; Lee, Jungil (Physics of Fluids, 2022)
In the present study, we perform an active proportional (P) feedback control of laminar and turbulent flows over a circular cylinder with an averaged velocity sensor to reduce its drag and lift fluctuations. As a sensor for the feedback control, we adopt an averaged transverse velocity on the centerline of the wake. For the averaging of the transverse sensing velocity, we consider both temporal averaging over a finite period and spatial averaging in the spanwise direction. As a control input, the blowing/suction actuation is provided on the cylinder surface near the flow separation, and its magnitude is linearly proportional to the averaged transverse sensing velocity. With the control, the fluctuations of the transverse sensing velocity are significantly reduced and the vortices right after the cylinder and the Kármán vortex shedding in the wake are weakened, resulting in substantial reductions of the mean drag and lift fluctuations. Furthermore, it is shown that the adoption of the averaged sensing velocity makes the P control successful for a wider range of sensing locations in laminar flow at Re = 100 and is essential for the success of the P control in turbulent flow at Re = 3900. With the optimal control parameters, the reductions of the mean drag and lift fluctuations for turbulent flow at Re = 3900 are about 11% and 61%, respectively. The present P control maintains the magnitude of the blowing/suction actuation less than 1% of the free-stream velocity, and thus, the control input power is very small, leading to an excellent control efficiency.
Keywords: Centerlines; Control inputs; Cylinder surface; Laminar and turbulent flow; Linearly proportional; Proportional feedback; Spatial averaging; Temporal averaging; Transverse velocity; Velocity sensor